Care practices favoring integral care to high-risk newborns: a systematic review - Duarte, Elysangela Dittz (2010)
doi: 10.5216/ree.v12i3.7509The search of a care that contemplates biological, psychic and social dimensions of the newborns has been promoted through different practical that we consider to be supporters of the integrality of health care.  A systematic literature review was carried out with the goal of identifying practices that favor the integrality of health care to high-risk newborns. A search was carried out in the databases BDENF, LILACS, MEDLINE, PAHO, WHOLIS and BVS INTEGRALIDADE, using the indexers Comprehensive Health Care, Neonatology, Newborn and Intensive Care Units, Neonatal, in the period between 1988 and 2009. Seventeen publications in English, Spanish and Portuguese were selected. Results were grouped in the following categories: newborn and family-focused care, multiprofessional teamwork, participation of the mother and the family members in newborn care and continuity of care. The conclusion was that initiatives are taken to make integral care possible; nevertheless, there are still hurdles to be overcome in order to build true integral assistance to high-risk newborns, especially with regards to widening care focus and reorganizing the work process in Neonatal Intensive Care Units. Descriptors: Comprehensive Health Care; Neonatology; Newborn; Intensive Care Units, Neonatal.